Frontispiece: Insight into the Mechanochemical Synthesis and Structural Evolution of Hybrid Organic–Inorganic Guanidinium Lead(II) Iodides. Issue 67 (2nd December 2018) - Wilke, Manuel; Casati, Nicola
Abstract : The reaction paths in the formation of four hybrid organic–inorganic guanidinium lead(II) iodides were followed by in situ synchrotron powder X‐ray diffraction measurements, revealing complex reaction mechanisms. The compounds show large differences in their respective nucleation and growth speeds, as evidenced by their interconversion and intermediate formation. These observations are related to the different arrangements of the inorganic‐organic moieties in the respective compounds, the crystal structures having been solved by powder X‐ray diffraction. They differ in composition, dimensionality of the inorganic framework and the strength of ionic interactions; a link is proposed between these features and the reaction mechanisms. For more details, see the Full Paper by N. Casati and M. Wilke onpage 17701 ff.